PEMBERDAYAAN MASYARAKAT WANITA TANI MELALUI PELATIHAN PENGOLAHAN UBI KAYU DI KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMAPULUH KOTA SUMATERA BARAT - Wenny Surya Murtius; Purnama Dini Hari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
This program partner is the member of Expectance Family Program (Program KeluargaHarapan/PKH) and cassava crackers (opak) female producers. The activity of processing cassava intocassava crackers were taken place in Nagari Tanjung Gadang while cassava leaf dendeng and cassavanugget processing were taken place in Nagari Ampalu. The counseling about food additive were also donein both places. Teh program were done by andragogy method (counseling and practicing). The result shownthat the program participants had the knowledge about food additive and its hazardous effect of the carelessusage. The fermentation and cassava processing into cassava crackers were done corresponding to rulesof sanitation, the processing equipments also possible to enhance productivity and sanitation of theprocessess. In coclusion, this program is able to increase cassava crackers processing productivity by 3times and to raise the income by 300%. The questionnaires given after the activity shown participants interest to initiate the production of dendeng cassava leaf and cassava nugget commercially.